Prospects and State of the Glass Industry in Saudi Arabia and a preliminary assessment of the quality of Glass and Glass-Ceramics Fabrication - Mahmoud, Essam R. I.; Shaharoun, Awaluddin Mohamed; Aljabri, Abdulrahman; Almohamadi, Hamad; Farhan, Mohammed (Mekanika: Majalah Ilmiah Mekanika, 2022)
The current study presents a feasibility study of the fabrication of ordinary glass and glass ceramics from Saudi Arabian domestic raw materials. It discussed the glass industry in Saudi Arabia and the middle east region. It also gives a brief explanation of the sand geography in Saudi Arabia. Also, it represents experimental data about the fabrication of ordinary glass and glass ceramics from Saudi raw materials. Firstly, ordinary transparent glass without significant defects was fabricated with sand collected from the Ar-Rays region in Saudi Arabia. Four nanosized crystallization catalysts, namely Vanadium Carbide (VC), Tungsten Carbide (WC), Titanium Carbide (TiC), and Titanium Oxide (T2O3,) were added to the constituents of the Glass in 3% wt. For VC, the crystallization process was limited. The glass ceramics of WC consisted of multi-dimensional edges crystals that covered all of the matrices. The addition of TiC obtained gray crystalline whiskers. The Y2O3-glass ceramics consisted of multi-directionally rosette crystals. Finally, the microhardness values of the added crystallization catalysts in glass ceramics were much higher than in ordinary glass.